(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal energy development in British Columbia (BC), Canada is currently focused on displacing diesel generation in off-grid coastal communities. BC has 434 km2 of sites with peak annual spring currents exceeding 1.5m/s and 52 km2 exceeding 2.5m/s. However, many of these sites are relatively shallow, experiencing large percentage changes in tidal elevation and have significant asymmetry in the flood and ebb current directions due to coastal channel geometry. Proposed projects are in the 50-250kW range and floating moored platforms are suitable as support structures for cost and operational simplicity reasons. This work addresses the design of a unique two-point flexible line mooring for a floating platform supporting a vertical axis turbine at Blind Channel Resort – a tidal demonstration site, located approximately 50 km north of Campbell River. A tidal turbine was previously moored by a rigid arm single-point mooring system at this site that, while effective in optimizing alignment with the current, relied on a submerged rotary electrical slip joint. The slip joint represented a significant point of failure, requiring frequent costly and inconvenient maintenance, given the remoteness of the site. The objective of this work is to replace the rigid single-point mooring and slip joint with a newly designed flexible two-point mooring system. By enhancing the system’s affordability and practicality, this new mooring design aims to make small scale, remote, tidal energy installations more viable across BC and other regions. This paper proposes an integration of highly compliant elastic members with traditional mooring line material and Dyneema, in a lazy-S configuration. During low current and low-tide situations, the elastic segments contract, drawing in the excess Dyneema line and preventing the mooring lines from entangling with the sea floor. As the current increases, the elastic segments stretch, and load is shifted onto the Dyneema line. To assess the design, a comprehensive set of tide and current scenarios are established based on data gathered at the site. Acoustic Current Doppler Profilers were utilized at the site and recorded current profiles for a cumulative 364 days. Using this data, five different current elevation profiles were selected as design load cases. System simulations were conducted with ProteusDS software. Initial slack tide simulations assessed the potential for mooring line entanglement with either the seafloor or other lines and provided initial equilibrium configurations of the system for subsequent simulations. The subsequent cases focused on the tidal turbine’s alignment under the five current profile scenarios to ensure that the appropriate alignment was met. Finally, transient simulations were utilized to measure bearing loads in the Dyneema and elastic mooring segments, verifying that the primary load is successfully transferred to the Dyneema as the mooring system extends during current transients. The proposed mooring system eliminates entanglement issues, maintains proper tidal turbine alignment across the full range of current profiles and tidal ranges, and ensures effective load management that meets both operational and safety requirements. This work demonstrates a promising mooring solution for advancing small-scale tidal energy installations in similar settings in BC and beyond.